1986
DOI: 10.21273/jashs.111.6.889
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss in Sweet Potatoes During Curing and Storage: Contribution of Transpiration and Respiration

Abstract: Cured sweet potatoes [Ipomoea batatas (L.) Lam] were stored successfully at 15.6°C and 90% RH for up to a year without sprouting. Contribution of respiration and transpiration to total weight loss was determined during curing and storage in 6 cultivars. Respiration rate was highest the day of harvest, decreased during curing, and continued to decrease at a slower rate during the first several months of storage, whereafter it remained constant (except for slight increases during the last several months in 2 cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Past studies have shown that most of the postharvest WL is caused mainly by water loss in transpiration, while the rest is caused by respiration in nutrition consumption [18]. In this study, peaches from different groups suffered a total WL ranging from 16% to 25% after 14 d of storage.…”
Section: In Vivo Preservative Effects Of Candidate Antagonistic Yeast...mentioning
confidence: 85%
“…Past studies have shown that most of the postharvest WL is caused mainly by water loss in transpiration, while the rest is caused by respiration in nutrition consumption [18]. In this study, peaches from different groups suffered a total WL ranging from 16% to 25% after 14 d of storage.…”
Section: In Vivo Preservative Effects Of Candidate Antagonistic Yeast...mentioning
confidence: 85%